The girl from the other side : Siúil, a Rún. Vol. 8 - Nagabe; MacFarlane, Ysabet Reinhardt (Seven Seas Entertainment, 2020)
"For Shiva's sake, another life must be sacrificed. Teacher thought he had steeled himself to commit the deed, but perhaps some lingering trace of his humanity stilled his hand. Unable to harm others, he realizes the only recourse is to instead sacrifice himself. But what remains once the soul is gone?"--